JOHN MILBANK's THEOLOGY OF THE "GIFT" AND CALVIN's THEOLOGY OF GRACE: A CRITICAL COMPARISON - Billings, J. Todd (Modern theology, 2005)
In his theology of the Gift, John Milbank advocates a theology of "reciprocity" between God and humanity, involving "active" rather than "passive" reception of the divine gift. Calvin and other Reformation theologians are criticized by Milbank as demeaning the role of the human partner by advocating "passivity" in the reception of grace. This essay compares Milbank's theology of the Gift with Calvin's theology of grace, showing how Calvin overcomes the schematic options of "passivity" or "reciprocity" in the divine-human relation, all the while holding much more in common with Milbank's concerns about sanctification and participation than has generally been recognized.